Physiological characteristics of youth synchronized skaters - Fischer, L. E.; Darby, L. A.; Morgan, A. L.; Tobar, D. A. (International Journal of Exercise Science, 2016)
Figure skating is a lifelong sport with participation rates increasing for skaters of all ages. Development within the five disciplines of figure skating (individual skating, synchronized skating, pairs skating, ice dancing, and theater on ice) has led to increased physical demands placed on skaters` bodies. As a result, focus on sport performance testing, training, and injury prevention specific to figure skating is increasing. The purpose of this study was to use field tests to describe the physical characteristics of synchronized skaters and to determine the relationships between these physiological characteristics and skating abilities. Anthropometric data were collected and field tests (sit-and-reach, vertical jump, hexagon, one-min sit-ups, one-min modified pushups, timed wall sit, and one-mile walk/run) were performed during off-ice fitness classes as part of synchronized skating camps. Participants were divided into Advanced (ADV) (n = 20; "intermediate and above") and Beginner (BEG) (n = 21; "juvenile and below") groups determined by their Moves in the Field (MITF) test levels. Significant differences were found between ADV and BEG groups for age, body weight, height, BMI, sit-and-reach (SR), and vertical jump height (VJ). Results from univariate statistics and paired t-tests (p MITF) may assist synchronized skating coaches in the design of off-ice training programs to improve on-ice skating performance.